Cytokinin-mediated processes promote heat-induced disease susceptibility of plants to bacterial pathogens - Shigenaga, Alexandra Marie, author; Argueso, Cristiana, advisor; Bush, Dan, committee member; Leach, Jan, committee member; Heuberger, Adam, committee member; Nishimura, Marc, committee member (Colorado State University. Libraries, 2021)
As global human populations continue to grow and temperatures are expected to rise, the pressure to increase food productivity and develop more stress-resistant crop varieties intensifies. Increased temperatures, a consequence anticipated as a result of global climate change, is expected to have an overall negative impact on crop productivity and agricultural systems. When exposed to non-optimal, high temperature conditions plant defense responses to pathogen attack are attenuated, leading to a process referred to here as heat-induced disease susceptibility. The plant growth hormone cytokinin is known to regulate responses to both biotic and abiotic pressures, making it an ideal target to study heat-induced disease susceptibility. The overarching goal of this dissertation was to understand the role of cytokinin in heat-induced disease susceptibility, to identify novel strategies to combat this process and design new ways to teach future generations about the impact of climate change on agricultural systems and science policy. First, I identified that a plant lacking a functional cytokinin signaling pathway, ahk2,3 mutated on the cytokinin signaling receptors AHK2 and AHK3, was less susceptible at elevated temperatures to the bacterial pathogen, Pseudomonas syringae pv. tomato DC3000 (Pst DC3000). My results show that ahk2,3 plants are less susceptible under high temperature conditions with Pst DC3000 populations proliferating at a lower rate compared to wild-type plants overtime, suggesting that heat-induced susceptibility is partially dependent on cytokininiii signaling. Our results show that differences in susceptibility under elevated temperatures of ahk2,3 and wild-type plants is not attributed to an increase in defense responses, but rather by a possible change in the availability of nutrients for Pst DC3000. Together the data reveals that under high temperature conditions cytokinin promotes late-physiological processes, centered around primary metabolism, that are contributing to increased pathogen proliferation. These results led to the identification of cytokinin-regulated genes that could be utilized for breeding efforts to obtain loss-of-heat induced disease susceptibility that could be translated to crop species. Second, I identified that another member of the Brassicaceae family, Brassica napus, also exhibited heat-induced disease susceptibility to the bacterial pathogen, P. syringae pv. maculicola (Psm ES4326). Gene expression analysis confirms that similar to Arabidopsis, B. napus plants increase cytokinin signaling in response to high temperature stress. To further address if cytokinin was important for heat-induced disease susceptibility of B. napus, I utilized a chemical approach. B. napus plants were sprayed with the cytokinin-signaling antagonist, PI-55, prior to inoculation and results show that a single application of PI-55 led to a loss of susceptibility under heat to Psm ES4326. Additionally, this application of PI-55 did not lead to any adverse vegetative growth parameters, suggesting a potential novel chemical approach to combat heat-induced disease susceptibility in Brassicaceae crops. Lastly, I constructed a new approach to teach future generations about the impact of climate change on plant diseases in agricultural systems. "Plant Diseases and Climate Change" is an active learning activity designed to give college students experience in synthesizing information and developing a solution, in the context of plant pathology. This exercise uses the issue of heat-induced susceptibility of rice in the Philippines to improve student understanding of the interactions between abiotic and biotic factors affecting global food security. By using an international agricultural pathosystem, I aim to inform students how environmental pressures can impact economically important plant systems, the role scientists and experts play in policy making to preserve food security, and the importance of agriculture on a global scale.